Effects of repeated blood donation on iron status of blood donors in Zimbabwe: A cross‐sectional study. Issue 4 (2nd November 2021) - Vhanda, Donald; Chinowaita, Frank; Nkomo, Sisodwa; Timire, Collins; Kouamou, Vinie
Abstract: Introduction: Iron deficiency is a major complication of repeated blood donation. However, most of the blood screening methods employed by blood collection agents do not include iron status markers, leading to possible subclinical iron deficiency. The aim of this study was to evaluate the effects of repeated blood donation on the iron status of this vulnerable population in Zimbabwe. Methods: All donors were categorized into groups based on number of donations made in the previous 2‐year period prior to enrolment into the study. Serum iron, total iron‐binding capacity (TIBC), and ferritin were analyzed on automated chemistry analyzers while transferrin saturation (TSAT) was calculated. The Wilcoxon rank‐sum and ANOVA tests were used to assess the variation of iron profiles by gender and frequency of donations. All data analysis was performed using Stata software v 13. Results: Study participants included 170 repeat donors and 20 first‐time blood donors. The median (IQR) age was 23 (19‐27) years, while the majority were males 57% (n = 109/190). The overall prevalence of iron deficiency and reduced iron stores was 12.6% and 38.9%, respectively. There were statistically significant differences between males and females in all the iron status parameters ( P < .05). TIBC increased with number of donations, while iron, ferritin, and TSAT decreased with increased number of donations. Conclusion: A high proportion of blood donors had iron deficiency despite being eligible to donate. Repeated blood donation may lead to substantial reduction in iron stores among blood donors. Inclusion of iron biochemical markers may enhance proper screening and monitoring of blood donors in Zimbabwe to prevent development of iron deficiency anemia.